Application of geostatistical methods in the spatio-temporal modeling of groundwater levels in the Sébaco Valley aquifer, Nicaragua. - Castillo Treminio, Bianka Guadalupe (2022)
[Introduction]: Georeferenced environmental information from environmental institutions is the basis for improving environmental management and sustainability in the Latin American and Caribbean region. [Objective]: To evaluate the spatio-temporal evolution of the water table using groundwater level data measured in the network of monitoring wells of the Sébaco Valley aquifer. [Methodology]: The fluctuation of groundwater levels was evaluated during the dry seasons from 2010 to 2018 (9 years) based on water level measurements collected from the network of monitoring wells of the Sébaco Valley aquifer. The geostatistical approach applied to this dataset to reveal the predictive models was the Empirical Bayesian Kriging (EBK) method. This method obtained a spatial representation of the phreatic surface of the aquifer and was subsequently used to calculate the velocity and acceleration of the water table. [Results]: During the period analyzed, water table acceleration maps showed mean values of -0.52 m/year. These values suggest that part of the aquifer is experiencing a decline in water table levels that could be rapidly aggravated by climatic events and increased demand of water resources. [Conclusions]: The approach used for quantitative assessment of groundwater levels is suitable for countries lacking a database of aquifer-specific hydraulic parameters.